Zirconia enrichment in zircon sand by selective fungus-mediated bioleaching of silica - Bansal, Vipul; Syed, Asad; Bhargava, Suresh Kumar; Ahmad, Absar; Sastry, Murali (Langmuir, 2007)
One of the important routes for the production of zirconia is by chemical treatment and removal of silica from zircon sand (ZrSixOy). We present here a completely green chemistry approach toward enrichment of zirconia in zircon sand; this is based on the reaction of the fungus Fusarium oxysporum with zircon sand by a process of selective extracellular bioleaching of silica nanoparticles. Since this reaction does not result in zirconia being simultaneously leached out from the sand, there is a consequent enrichment of the zirconia component in zircon sand. We believe that fungal enzymes specifically hydrolyze the silicates present in the sand to form silicic acid, which on condensation by certain other fungal enzymes results in room-temperature synthesis of silica nanoparticles. This fungus-mediated twofold approach might have vast commercial implications in low-cost, ecofriendly, room-temperature syntheses of technologically important oxide nanomaterials from potentially cheap naturally available raw materials like zircon sand.

Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Intracellular synthesis of gold nanoparticles using alga tetraselmis kochinensis - Senapati, Satyajyoti; Syed, Asad; Moeez, Sana; Kumar, Ashutosh; Ahmad, Absar (Materials Letters, 2012)
The development of eco-friendly synthesis protocol for the synthesis of nanoscale materials of different compositions, shapes and sizes is an important area of research in the field of nanotechnology. In this paper, we report on the use of alga Tetraselmis kochinensis in the intracellular synthesis of gold nanoparticles of dimensions 5-35 nm. The particles are more concentrated upon the cell wall than on the cytoplasmic membrane, possibly due to reduction of the metal ions by enzymes present in the cell wall and cytoplasmic membrane. These intracellular nanoparticles may have applications in drug delivery, biomedical applications, catalysis, etc. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Algae; Biosynthesis; Nanoparticles; nanotechnology; Tetraselmis kochinensis

Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver

Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Preparation, spectroscopic characterization, theoretical investigations, and in vitro anticancer activity of Cd(II), Ni(II), Zn(II), and Cu(II) complexes of 4(3H)-quinazolinone-derived schiff base - Ashok, Ubale Panchsheela; Kollur, Shiva Prasad; Anil, Nishad; Arun, Bansode Prakash; Jadhav, Sanjay Namdev; Sarsamkar, Sanjay; Helavi, Vasant Baburao; Srinivasan, Asha; Kaulage, Sandeep; Veerapur, Ravindra; Al-Rashed, Sarah; Syed, Asad; et al. (Molecules, 2020)
Herein, we report the synthesis and characterization of a new Schiff base ligand 3-[[(E)-(3-hydroxyphenyl)-methylidene]amino]-2-methyl-quinazolin-4(3 H)-one (HAMQ) and its Cd(II), Ni(II), Zn(II), and Cu(II) complexes (C-1-C-4). The ligand HAMQ was synthesized by reacting 3-hydroxybenzaldehyde and 3-amino-2-methyl-4(3H)-quinazolinone in a 1:1 molar ratio. The structure of the ligand and its complexes (C-1-C-4) were evaluated using ultraviolet (UV)-visible (Vis) light spectroscopy, H-1-NMR, Fourier-transform infrared (FT-IR) spectroscopy, MS, elemental analysis, conductance data, and thermogravimetric analysis (TGA). The characterization results suggested that the bidentate ligand, HAMQ, coordinated to the metal center through the lactum oxygen and the azomethine nitrogen. Moreover, all the metal complexes were analyzed using powder X-ray diffraction studies, which revealed that all of them belong to a triclinic crystal system. The research was supplemented by density functional theory (DFT) studies on the IR and UV-Vis spectra, as well as the chemical reactivity of the HAMQ and its four metallic derivatives making use of conceptual density functional theory (CDFT) by means of KID (Koopmans in DFT) methodology. The synthesized complexes displayed significant in vitro anticancer activity against human cancer cell lines (HeLa and HCT-115).
Keywords: 3-quinolin-4(3H)-one; chemical reactivity properties; conceptual DFT; Metal complexes; spectral studies

Biological synthesis of alpha-Ag2S composite nanoparticles using the fungus Humicola sp. and its biomedical applications - Syed, Asad; Saedi, Marzouq Hussain Al; Bahkali, Ali H.; Elgorban, Abdallah M.; Kharat, Maheshkumar; Pai, Kalpana; Ghodake, Gajanan; Ahmad, Absar (Journal of Drug Delivery Science and Technology, 2021)
Synthesis of alpha-Ag2S (silver sulfide) is a highly challenging task, usually attempted using synthetic, hazardous chemical processes. This report puts efforts to exploring microbial-based eco-friendly alternatives. A facile, onepot biological method for the synthesis of alpha-Ag2S composite nanoparticles (NPs) in an aqueous medium at ambient conditions was established. As prepared alpha-Ag2S composite NPs were efficiently produced from precursors silver nitrate and sodium sulfite. The extracellular biomolecules produced by Humicola sp. reduced the precursor solution and at the same time it capped the formed Ag2S NPs. The characterization performed by different techniques revealed excellent optical, morphological, and structural properties (size, shape distribution, and crystallinity) of the alpha-Ag2S NPs. The change in color from colorless to dark brown indicated the formation of alpha-Ag2S, which was further confirmed by fluorescence and UV-Visible spectroscopy, showing a sharp peak at 410 nm. Morphological analysis of alpha-Ag2S NPs confirmed the spherical shape, and narrow size distribution. alpha-Ag2S NPs were found to be potent in antimicrobial applications owing to their high dispersibility in water and capping by extracellular biomolecules secreted by Humicola sp. The anti-cancer activity for alpha-Ag2S performed using human breast cancer cell line (ZR-75-1) and human Burkitt's lymphoma cancer (Daudi). The biocompatibility test was performed using human peripheral blood mononuclear cells (PBMCs) for alpha-Ag2S NPs. The anti-leishmania activity was also determined for alpha Ag2S NPs in-vitro using the standard anti-promastigote protocol (Leishmania donovani promastigotes). This extracellular system is an economically and environmentally benign route for the biosynthesis of alpha-Ag2S NPs having desired surface, structure and biomedical properties.
Keywords: Cytotoxicity; Fungus; Hemolysis; Humicolasp; Silver sulfide(alpha-Ag2S)

Alpha Au2S nanoparticles: fungal-mediated synthesis, structural characterization and bioassay - Syed, Asad; Al Saedi, Marzouq H.; Bahkali, Ali H.; Elgorgan, Abdallah M.; Kharat, Mahesh; Pai, Kalpana; Pichtel, John; Ahmad, Absar (Green Chemistry Letters and Reviews, 2022)
Luminescent nanoparticles synthesized via bio-based protocols that generate nanoparticles having different chemical compositions along with other functionalities (size and morphology) have received huge attention. We have focused our research on gold sulfide nanoparticles (Au2S NPs) and have biosynthesized these NPs using the fungus Humicola sp. The nanoparticles were characterized by Transmission Electron Microscopy, which showed spherical morphology of Au2S. UV-Visible-NIR spectrophotometry, luminescence spectrophotometry, Selected Area Electron Diffraction, Energy Dispersive Analysis of X-rays, and X-ray diffraction were performed. FTIR confirmed that the fungal metabolites including biomolecules secreted in the reaction medium are primarily responsible for nanoparticle synthesis and stabilization. The fungus reduced the precursor solution (HAuCl4 and Na2SO3) and at the same time capped them with secreted biomolecules. The anti-leishmanial activity of Au2S NPs was determined against L. donovani promastigote (Ag83 strain). Au2S NPs displayed less cytotoxicity towards both normal and cancer (Daudi, ZR-75-1) cell lines. Hemocompatibility was determined via hemolysis assays. This novel fungal-based system demonstrates an economical and environmentally benign process for biosynthesis of Au2S nanoparticles which may find application in bioimaging and labeling studies.
Keywords: Biosynthesis; Cytotoxicity; Gold sulfide; Hemolysis; humicola sp; promastigote